Collegiate rowing crew performance varies by morningness-eveningness - Brown, F. M.; Neft, E. E.; LaJambe, C. M. (The Journal of Strength and Conditioning Research, 2008)
During adolescence and early adulthood, most humans are predisposed developmentally, both biologically and socially, toward evening/night activity. The morningness-eveningness (M-E) tendency to be an evening-preferring (E-type) rather than a morning-preferring (M-type) or intermediate/neither (N-type) "chronotype" may affect athletic performance at various times of day. This study evaluated M-E effects on rowing performance of an intact, experienced, university club crew with near-daily early morning (0500-0700 hours) and late afternoon (1630-1800 hours) training schedules. The hypothesis tested was that chronotype would modify circadian effects during morning and afternoon performances. Eight men and eight women (mean age 19.6 +/- 1.5 years) were tested in a randomized, counterbalanced design. A standard qualifying 2000-m ergometer rowing sprint and a nonroutine standing broad jump task were measured during early morning and late afternoon, separated by 3 days of rest. Each subject's chronotype was determined using two standard self-rating M-E scales, resulting in eight E-type (three women/five men), four M-type (two women/two men), and four N-type (three women/one man) subjects. The rowing results show that E-type and N-type subjects did not differ between morning and afternoon rowing performances, whereas M-type subjects rowed significantly faster in the morning. In contrast, the standing broad jump showed no consistent time-of-day or chronotype effect. These findings suggest that basic performance timing in young athletes is determined to some extent by naturally occurring M-E predispositions. Further, modification of time-of-day influences may be possible by routine practice at the same time each day, as was suggested here by the absence of evening superiority in performances. Understanding their personal M-E tendencies could allow young athletes to arrange training schedules at specific times of day to help counteract any natural circadian influences that might work against their performance.